Evaluating the Awareness and Knowledge about Probiotics in Postgraduate Students of an Indian Dental College - Kumari Upasana; Rameet Sandhu; Prerna Kataria; Abhik Sinha; Ritesh Vatsa; Nisha Parveen (Journal of Pharmacy and Bioallied Sciences)
Background: Probiotics are vital in maintaining gut health. With increasing drug resistance, it is crucial to keep healthy gut microbes, making probiotics essential. Aim: This study aimed to assess the awareness and knowledge of probiotics among postgraduate students of an Indian dental college. Methods: This observational study utilized an online self-administered questionnaire, which was developed using a thorough review of the literature, consisting of 19 questions divided into three parts. The term probiotics was also assessed as general commercial compositions of both probiotics and prebiotics. The data gathered were analyzed statistically. Results: Postgraduate dental students were well aware of probiotic terms from TV or newspapers; however, necessary technical specifications were not known during purchase and were not familiar with trade names of probiotic preparations in the market. Conclusion: Students have good knowledge of probiotics and associated health benefits but technical information concerning commercial probiotics is lacking.